The reality test of residence goes through the looking glass: Court of Justice of the European Free Trade Association States (EFTA Court), judgment of 26 July 2016, Case E-28/15, 'Yankuba Jabbi' v 'The Norwegian Government, represented by the Immigration Appeals Board' - Bierbach, Jeremy B (European constitutional law review, 2017)
In July 2016, the EFTA Court issued a judgment on the circumstances under which EEA law provides for a derived right of residence in the home member state of an EEA national for the third-country national family member of that EEA national, specifically when that EEA national has returned from residing in another EEA state as an economically inactive person. In this, the Court was adding its own translation into EEA law (at least as it applies to the EFTA states, the three member states of the EEA that do not belong to the EU: Norway, Liechtenstein and Iceland) onto a veritable tower of case law from the European Court of Justice, its EU counterpart, starting with 'Surinder Singh', going on to 'Eind', and most recently restated in 'O and B'.